Anti-inflammatory labdane-type diterpenoids from Physalis angulata. Issue 80 (16th August 2016) - Sun, Cheng-Peng; Yuan, Ting; Wang, Lei; Kang, Ning; Zhao, Feng; Chen, Li-Xia; Qiu, Feng
Abstract : Twelve new labdane-type diterpenoid glycosides were isolated from the stems and leaves of P. angulata . Abstract : The investigation for stems and leaves of Physalis angulata led to the isolation of twelve new labdane-type diterpenoid glycosides, physangulatosides A–L (1–12 ). Their structures were established on the basis of NMR, IR, UV, and HRESIMS spectra. All isolated compounds were assayed for inhibitory activities against LPS-induced NO production in RAW 264.7 macrophages. Compounds6–10 displayed inhibitory effects against NO production with IC50 values of 15.9 ± 1.0–60.7 ± 3.8 μM. Herein, a plausible biosynthetic pathway for compounds1–12 was also discussed.